Electrodes modified with electroinactive layers: distinguishing through-film transport from pinhole (pore) diffusion. - Menshykau, D; Compton, R (2009)
Electrodes modified with layers, for example, of polymers or self-assembled monolayers, are of great importance from both the fundamental and applied points of view. Two different models of electrodes covered with electroinactive layers can be proposed. First, the electrode is covered with a uniform layer into which the electroactive species dissolves and then diffuses through, or second, the layer contains pinholes that are exclusively responsible for diffusional transport to the electrode. Both models are simulated and then compared to identify conditions under which they can be distinguished. The models are studied for a broad range of parameters reflecting experimentally viable values. Different types of cyclic voltammograms can be observed in the studied models corresponding to classical Randles-Sevcik, thin layer, and steady-state behaviors. We show that the models can be distinguished experimentally through recording cyclic voltammograms over a sufficiently broad range of voltage scan rates.